Kesiapan Sekolah Menjadi Inklusi (Studi SMA Negeri Kota Kendari) - Nasir; Isak Bagea; Rulis (Kelola: Jurnal Manajemen Pendidikan, 2025)
This study aims to explore the readiness of schools in implementing inclusive education in Kendari City and to analyze strategies that can be applied to address implementation challenges in the field. The research employed a qualitative method with a case study approach. Data were collected through Focus Group Discussions (FGDs) involving education experts, representatives from the Education Department, principals of Special Schools (SLB), as well as teachers and principals from several senior high schools in Kendari City. Observations were also conducted based on aspects outlined in the General Guidelines for Inclusive Education Implementation as stated in Ministry of National Education Regulation No. 70 of 2009. The results show that school readiness varies significantly. Most schools lack adequate human resources and facilities, although some have established partnerships with SLBs and participated in inclusive education socialization programs. Key challenges include insufficient teacher training, limited infrastructure, and low public awareness. Recommended strategies include teacher capacity-building, provision of accessible facilities, policy support, and public education. This study underscores the importance of collaborative approaches among stakeholders to realize a fair and sustainable inclusive education system.